Language characteristics illustrating mass suicide in the destructive cult sermons - Palayon, Raymund T.; Todd, Richard Watson; Vungthong, Sompatu (Humanities, Arts and Social Sciences Studies, 2024)
Destructive cults remain a significant focus in religious research due to their extreme behaviours and tragic outcomes. Among the most notorious were Peoples Temple led by Jim Jones and Heaven’s Gate led by Marshall Applewhite. They shocked the world by committing mass suicide. Previous studies have mainly focused on the psychological and behavioural aspects of these groups, particularly in the context of these tragic events. This paper examined the meaningful linguistic features in Jim Jones’ sermons and Marshall Applewhite’s sermons in the period leading up to the mass suicide. By comparing them to the mainstream sermons and sect sermons using keyword and collocation analysis, distinct patterns emerged. Jim Jones’ sermons contain words associated with negative sociopolitical views (such as socialism, communism, war, violence, and killed), which allowed Peoples Temple to express mass suicide literally. In contrast, Marshall Applewhite’s sermons contain implicative words associated with distance and movements (such as heavenly, planet, vehicle, overcoming, and separate), enabling Heaven’s Gate to express mass suicide in a figurative manner. Both sermons apply communication styles where three styles: othering (we, they), intensification (very, really), and negation (can’t) are common in the two datasets, allowing each leader to convey mass suicide. The findings guide us to characterize the behavioural effects of mass suicide and these provide communication signs to identify the dangerous characteristics of suspicious religious groups before their destructive activities happen.